Screening by mode of trade - Juan Beccuti; Marc Möller (University of Bern, Department of Economics, 2019)
This paper proposes a mechanism design approach, capable of endogenizing a monopolist's choice between selling and renting in a non-anonymous durable goods setting with short-term commitment. Allowing for mechanisms that determine the good's allocation not only at the beginning but also at the end of a given period, we show that the profit-maximizing mechanism features screening by mode of trade. By selling to high types while renting to low types, the monopolist overcomes the obstacles encountered by intertemporal price discrimination and induces immediate separation of types for arbitrary low priors.
Keywords: D82; D86; D42; 330; Durable goods; Dynamic mechanism design; Coase problem; Ratchet effect; Screening